A venue for the end of the world - Prewett, Aidan; Devil Blue Films; Soundview Media Partners ([Melbourne, Australia] : Devil Blue Films, 2014)
What does it feel like to have half a million people in the palm of your hand? Haunted by uncanny similarities between Nazi stage techniques and the showmanship employed by modern entertainers, a filmmaker investigates the dangers of audience manipulation and leader worship. --
Originally released as a documentary motion picture in 2014.
Featuring interviews with Dick Cavett, Ian Anderson, Joe Mcdonald, Paul Provenza, Ted Leo, Dale Bell, John Binder, Jeanne Field, Evan Gregory, Sarah Gregory, D.A. Pennbaker and others.
Cinematographers, Aidan Prewett, Schy Peterson
In English.
Winner of an Award, at Highway 61 International Film Festival 2015 : Best Documentary
Winner of an Award, at Melbourne Underground Film Festival 2014 : Best Documentary
Keywords: Leadership -- Moral and ethical aspects; United States -- Social conditions; Propaganda; Arenas; Music facilities; Documentary films; Nonfiction films; Internet videos; Streaming video